The slayers of Moses : the emergence of rabbinic interpretation in modern literary theory - Handelman, Susan A. (SUNY series in modern Jewish literature and culture., 1982)
"In this groundbreaking study, Susan Handelman examines the theological roots of the modern science of interpretation. She defines current structures of thought and patterns of organizing reality, clearly distinguishes them from previously reigning Hellenic modes of abstract thought, and connects them with important elements of the Rabbinic interpretive tradition. Hers is the first comprehensive treatment of the undeniable, and undeniably significant, influence of Jewish religious thought on contemporary literary criticism. Dr. Handelman shows how they provide a crucial link among several of the most influential modern theories of textual interpretation, from Freud to the Deconstructionist School of Lacan and Derrida, as well as current literary theorists who revive Rabbinic hermeneutics, such as Harold Bloom and Geoffrey Hartman.Susan A. Handelman, Assistant Professor of English at the University of Maryland, has published articles on literature, critical theory, and Jewish studies."--